The effect of L-Carnitine injections on some semen characteristics of male Afghan goats (Tikrit Journal of Veterinary Science, 2024)
The aim of the study is to improve the semen characteristics of Afghan goats. This study was conducted in the animal field of the Department of Animal Production/College of Agriculture/University of Diyala during the period from 10/6/2022 until 10/9/2022, and microscopic examinations of semen were conducted in the physiology laboratory of the Department of Animal Production. It was done in the Al-Amin Medical Laboratory For pathological analyses/Baquba, the experimental animals were randomly divided into four groups and four replicates for each group. The first group was without injection (the comparison) and the other three groups were injected with different concentrations of L-carnitine every three days. My agencies: The second group was injected with 25 mg of L-carnitine/kg body weight. The third group was injected with 50 mg of carnitine/kg body weight, and the fourth group was injected with 75 mg of carnitine/kg body weight. The animals were trained in the process of collecting semen for 10 days before the tests began. At the end of each month, semen was collected and semen tests were performed.     The results of the study showed that injection of L-Carnitine at a concentration of 75 mg led to a significant increase in the volume of ejaculate, the mass matility of sperm, the individual movement of normal sperm, the concentration of sperm, the percentage of live sperm, and the percentage of live, dead, and deformed sperm.